2020
DOI: 10.1097/rhu.0000000000001276
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Atorvastatin in Patients With Stable Systemic Autoimmune Myopathies

Abstract: Background/Objective: Patients with systemic autoimmune myopathies (SAMs) have high prevalence of dyslipidemia and, consequently, possible endothelial dysfunction and vascular stiffness. Our objective was to evaluate the possible benefits on endothelial function and vascular stiffness, as well as adverse effects of atorvastatin in SAMs.Methods: A pilot longitudinal, double-blind, randomized, placebo-controlled study was conducted. Twenty-four of 242 patients were randomized at a 2:1 ratio to receive atorvastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(59 reference statements)
2
1
1
2
Order By: Relevance
“…Similarly, studies showed that autoimmune diseases especially the muscle-related ones were significantly associated with higher risk for SAMS. 37 Also, studies suggested that diabetes mellitus type 2, renal diseases, and liver dysfunction were significantly associated with SAMS which contradict our results as we did not find any association between these comorbidities and SAMS. 38 Moreover, our analysis showed that patients taking antiepileptic medications had significantly higher risk of SAMS compared with their counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, studies showed that autoimmune diseases especially the muscle-related ones were significantly associated with higher risk for SAMS. 37 Also, studies suggested that diabetes mellitus type 2, renal diseases, and liver dysfunction were significantly associated with SAMS which contradict our results as we did not find any association between these comorbidities and SAMS. 38 Moreover, our analysis showed that patients taking antiepileptic medications had significantly higher risk of SAMS compared with their counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…From a laboratory point of view, a previous study 15 showed that the use of atorvastatin did not promote alterations in serum glucose, insulin, and C‐peptide levels, evaluating the HOMA index and corroborating the data obtained at the molecular level in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…According to a study carried out in patients without SAMs who used statins, this class of medications, even if rarely, can induce the release of COX, which may be responsible for the formation of apoptosomes and consequently cause cell apoptosis. 11 From a laboratory point of view, a previous study 15 showed that the use of atorvastatin did not promote alterations in serum glucose, insulin, and C-peptide levels, evaluating the HOMA index and corroborating the data obtained at the molecular level in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Foram coletados, em período menor do que uma semana após a entrevista dos pacientes, no tempo 0 (início do estudo), e na 12ª semana, amostras de soro (10 mL de soro e de plasma) para análise de CPK, AST, ALT, DHL, além de colesterol total, HDL-colesterol, LDL-colesterol, triglicerídeos, glicemia de jejum, insulina e resistência à insulina (Homeostatic Model Assessment: HOMA) (78). Esses dados estão publicados em artigo prévio (72).…”
Section: Materiais E Métodosunclassified